Normative data for the Strengths and Difficulties Questionnaire for young children in Australia. (14th April 2015) - Kremer, Peter; de Silva, Andrea; Cleary, Joyce; Santoro, Giuseppe; Weston, Karen; Steele, Emily; Nolan, Terry; Waters, Elizabeth
<x xml:space="preserve">Abstract</x> Aim The aim of this study was to report normative data for the parent‐reported Strengths and Difficulties Questionnaire (SDQ) from a large population cohort of young children aged 4–6 years from Victoria, Australia, to establish age‐ and sex‐specific cut‐off values for future use, and to determine the scale reliability of the SDQ for children aged 4–6 years. Methods Parents of children (n = 53 372) entering their first year of school in Victoria in 2010 completed a survey via a 15‐page School Entrant Health Questionnaire reporting on the physical and emotional well‐being of their child (including the SDQ), use of child health and other support services, and a range of socio‐demographic variables. Reliability was assessed and norms generated. Appropriate cut‐off values for each SDQ scale and total difficulties scale were generated for each age group separately for each sex. Results The five scales of the SDQ and total difficulties scale generally had acceptable internal reliability. Mean SDQ scale scores differed for both sex and age, although only a narrow age range is examined in this study. Cut‐off values were marginally higher for girls (lower for prosocial) and generally increased with age. Conclusions This study has utilised a large Australian population sample of children to generate age‐ and sex‐specific cut‐off values that define SDQ scores as 'normal', 'borderline' or 'abnormal' for Australian children aged 4–6 years.